PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI PT ADHYA MAHKOTA GOLF SUKAJADI BATAM - L, Nilasari; Syaifullah, Syaifullah (SCIENTIA JOURNAL, 2019)
This study aims to determine the effect of price and service quality on customer satisfaction directly. This research was conducted at PT Adhya Mahkota Golf Sukajadi Batam. This research is motivated by frequent complaints from customers, slow service to customers and not friendly in serving customers. This study aims to determine the effect of price and service quality on customer satisfaction Sukajadi Golf Course at PT Adhya Mahkota Golf S in Batam. The population this study customers of PT Adhya Mahkota Golf Sukajdi Batam playing golf at Sukajadi Golf Course. The sample in this study reached 154. The results analysis show that there is effect of price variable (X1) customer satisfaction (Y), it can be proved in the t test which shows tcount 6.779> ttable 1.97569 and significant 0.000 <0.05 positive and significant. Service Quality Variable (X2) customer satisfaction (Y), can be proven in the t test where it shows tcount 5.889> t table 1.97569 and significant 0.000 <0.05 positive and significant. Price (X1) and Service Quality (X2) have a simultaneous effect customer satisfaction (Y) with Fcount 366,197> Ftable 3.05 and value is significant at 0,000 <0.05 together have significant effect customer satisfaction.